Multi-Ring Structure of the Eclipsing Disk in EE Cep - Possible Planets? - Gałan, C.; Mikołajewski, M.; Tomov, T.; Świercyński, E.; Wicecek, M.; Brożek, T.; Maciejewski, G.; Wychudzki, P.; Hajduk, M.; Różański, P.; Ragan, E.; Budzisz, B.; et al. (Binaries - Key to Comprehension of the Universe, 2010)
The photometric and spectroscopic observational campaign organized for the 2008/9 eclipse of EE Cep revealed features, which indicate that the eclipsing disk in the EE Cep system has a multi-ring structure. We suggest that the gaps in the disk can be related to the possible planet formation.
Keywords: Astrophysics - Solar and Stellar Astrophysics